ARCHITECTURAL AND ECONOMIC APPROACH TO LOW-RISE HOUSING TO ACHIEVE ECONOMIC STABILITY AND SUSTAINABLE DEVELOPMENT - Олексій Ященко; Дмитро Макатьора; Руслан Кубанов (Економіка та суспільство, 2023)
Sustainable construction, in the context of sustainable development at economic, social and environmental levels, is a proven strategy that responds to the challenges of the modern construction industry. It is an approach that focuses on balanced development, taking into account the needs of the present without compromising the needs of future generations. At the economic level, sustainable construction contributes to the creation of efficient and energy-saving buildings, which helps to reduce heating and cooling costs. It also reduces the impact of construction on financial resources through the use of more cost-effective materials and technologies. This research aims at identifying theoretical concepts and practical ways of economic, environmental and construction development of architectural and economic concept of low-rise buildings for achieving economic stability and sustainable development of the country. In order to create the concept of sustainable development, it is recommended to base it on the circular economy model. This model provides for the reuse of materials. The unacceptability of using materials that cannot be reused is the main principle of this model. This means that, without producing waste or polluting the environment, resources should be used efficiently and in a circular manner. It should be noted that the cost of building houses and apartments in this type of development needs to be identified in detail when analysing the cost of low-rise development. The cost of developing infrastructure such as engineering and transport, and the cost of maintaining engineering networks and transport communications must also be considered. In general, the feasibility study also includes the cost of land and legal regulation. According to the authors, maximum economic efficiency can be achieved by concentrating on developing two to four-storeyed buildings. In low-rise residential buildings, there are two ways to save energy. Firstly, by reducing energy consumption from external sources through the installation of autonomous or local technical systems. Secondly, by using energy-efficient buildings that use alternative energy sources, energy savings can be achieved. One of the key concepts of modern housing is considered to be the active house. This means that modern economic concepts need to be applied. For example, the principle of “zero waste” and the model of a circular economy based on this principle require that the generation of waste be reduced or avoided as much as possible. In the case of old buildings, the principle of zero waste means that these buildings should be easy to dismantle without generating a significant amount of waste. One of the possible uses of these materials is to create new building materials or to produce other goods. The conclusions show that economic resilience, sustainable development and improved quality of life in the country can be achieved by using the architectural and economic concept of low-rise buildings. This has great potential to create a sustainable and prosperous society in the future, but requires an integrated approach and collaboration between different stakeholders.